Exploring student learning outcomes in physics learning using a problem-based learning model with a differentiated learning approach - Jafriansen Damanik; Novita Nabilla; Ridwan Abdullah Sani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to determine differences in student learning outcomes in physics lessons by applying a problem-based learning (PBL) model that uses a differentiated learning approach compared to conventional learning. This research uses quasi-experimental methods in the form of a two-group pretest-posttest design. This study used a sample of 40 students from 2 classes of XI PMIPA: 20 students for the control class and 20 for the experimental class. Research data consists of student learning outcomes using descriptive and comparative analysis supported by test requirements analysis that includes normality, homogeneity, and N-Gain. The results indicated that student learning outcomes score higher with the PBL model using a differentiated learning approach than the conventional learning model. The difference in scores between the two is significant. It means that implementing the PBL model based on a differentiated learning approach can improve student learning outcomes. Thus, this research suggests that the PBL model uses a differentiated learning approach that can be relied upon to improve student learning outcomes, so teachers need to use the PBL model more intensively based on a differentiated learning approach to encourage increased student learning outcomes in physics.